The Effect of Sustainability Reports, Capital Structure and Profitability Influence the Market Value of Indonesia Manufacturing Companies - Rangkuti, May Hana Bilqia; Sari, Fauziah Kumala (JASa (Jurnal Akuntansi, Audit dan Sistem Informasi Akuntansi), 2025)
This study examines the effect of sustainability reports, capital structure, and profitability on the market value of manufacturing companies in Indonesia. The success in increasing company value impacts investor confidence; therefore, this study investigates whether sustainability disclosure, capital structure, and profitability contribute to firm valuation. The research population includes manufacturing firms listed on the Indonesia Stock Exchange (IDX) that received the PROPER award from the Ministry of Environment during 2017–2022. This study applies a quantitative approach using secondary data from audited financial reports, annual reports, and PROPER assessments. The analysis technique employed is Partial Least Squares (PLS) with SmartPLS 3.0. The results indicate that sustainability reports and profitability have a positive but insignificant effect on market value, while capital structure measured by the debt-to-equity ratio shows a negative and insignificant effect. These findings suggest that investors in Indonesia have not yet fully integrated non-financial disclosures and profitability measures into their valuation decisions. The study concludes that improving transparency in sustainability reporting and maintaining an optimal capital structure could enhance long-term firm value and strengthen investor trust.